The Impact of Intangible Assets on Capital Structure: An Empirical Data of Thai Listed Companies - Xu, Xining; Swatdikun, Trairong; Chen, Xiaoque (Science, Technology, and Social Sciences Procedia, 2024)
In the dynamic landscape of the capital market, the phenomenon of asymmetric information poses intriguing challenges for scholars and practitioners alike. This study delves into the intricate interplay between intangible assets and capital structure within the context of the Thai stock market. By examining a robust sample comprising 767 companies spanning eight diverse industries in Thailand during the fiscal year 2019, this research endeavors to enrich the existing discourse on capital structure determinants. Our findings underscore the pivotal role of intangible assets in shaping capital structure dynamics, echoing prior empirical evidence. Notably, the negative association between intangible assets and capital structure suggests their profound implications in optimizing financial decisions, warranting vigilant scrutiny and strategic consideration.